S100A1 gene therapy for heart failure: A novel strategy on the verge of clinical trials - Rohde, David; Brinks, Henriette; Ritterhoff, Julia; Qui, Gang; Ren, Shumei; Most, Patrick (Journal of molecular and cellular cardiology, 2011)
Representing the common endpoint of various cardiovascular disorders, heart failure (HF) shows a dramatically growing prevalence. As currently available therapeutic strategies are not capable of terminating the progress of the disease, HF is still associated with a poor clinical prognosis. Among the underlying molecular mechanisms, the loss of cardiomyocyte Ca2+ cycling integrity plays a key role in the pathophysiological development and progression of the disease. The cardiomyocyte EF-hand Ca2+ sensor protein S100A1 emerged as a regulator both of sarcoplasmic reticulum (SR), sarcomere and mitochondrial function implicating a significant role in cardiac physiology and dysfunction. In this review, we aim to recapitulate the translation of S100A1-based investigation from first clinical observations over basic research experiments back to a near-clinical setting on the verge of clinical trials today. We also address needs for further developments towards “second-generation” gene therapy and discuss the therapeutic potential of S100A1 gene therapy for HF as a promising novel strategy for future cardiologists. This article is part of a Special Section entitled “Special Section: Cardiovascular Gene Therapy”.
Available online 20 August 2010
Gesehen am 19.09.2022